Economic implications of citrus greening disease management strategies - Zapata, Samuel D; Peguero, Felipe; Sétamou, Mamoudou; Alabi, Olufemi J (2022)
Citrus greening (HLB) is an incurable bacterial disease severely affecting most citrus production regions. Evaluating the economic feasibility of control practices is challenging due to the complex intertemporal interactions among the pathogen, the vector, and the host. We propose a stochastic evaluation framework to systematically analyze the long-term economic performance of a broad range of management strategies. Different control approaches are evaluated in a hypothetical application in Texas. Results highlight the detrimental effects of the disease and the importance of developing cost-effective control options. A substantial loss in value is expected regardless of the intervention actions implemented.